Application of Work Safety and Health Management Systems in the Technical Implementation Center of Primary Health Care Bendilwungu, Tulungagung, East Java - Muhamad Taufiqurrahman; Ratna Wardani (Journal for Quality in Public Health, 2020)
Background. The Occupational Safety and Health Management System in Fasyankes is part of the overall Health Services Facility management system in the context of risk control related to work process activities in the Health Services Facility in order to create a healthy, safe, safe and comfortable work environment. The purpose of this research is to explore the implementation, evaluation process, impact and expectation of SMK3 in Primary Health Care Bendilwungu Tulungagung Method. Based on the type of this research is a qualitative research to describe the implementation of SMK3 at Primary Health Care Bendilwungur. Another supporting instrument uses an instrument in the form of a list of questions containing semi-structured questions. The research informants numbered ten and four. Research Triangulation at the Puskesmas. Other tools used are friends, field notes, cellphones, then documented in the form of transcripts (field notes). Data processing was carried out by means of content analysis. Furthermore, it is reported and presented in a descriptive description in relation to the theory. Results. The results of the study indicate that the application of SMK3 in the Primary Health Care Bendilwungu has been running from the end of 2018 as indicated by the existence of the SK Head of the Puskesmas as a guideline and legal umbrella in implementing the implementation of SMK3 in the Puskesmas. In the process of implementing and implementing SMK3 in the Puskesmas there are basic obstacles namely that there is no calm of K3 and SMK3 professionals and the joining of the SMK3 Implementation Unit with Patient Safety and the lack of knowledge and understanding of K3 and SMK3 to several Puskesmas employees. Conclusion. The Primary Health Care Bendilwungu needs to improve its discrepancies in the application of SMK3 and provide training and guidance on K3 and SMK3 to employees so as to always improve the OHS work standard supervision at the Primary Health Care Bendilwungu and make K3 a work culture.